Synergistic application of melatonin and silicon oxide nanoparticles modulates reactive oxygen species generation and the antioxidant defense system: a strategy for cadmium tolerance in rice - Faisal, Mohammad; Faizan, Mohammad; Soysal, Sipan; Alatar, Abdulrahman A. (Frontiers in Plant Science, 2024)
The main objective of this study was to observe the protective role of melatonin (Mel) and silicon oxide nanoparticles (SiO-NPs) in rice (Oryza sativa L.) seedlings under cadmium (Cd) stress. Rice seedlings have reduced growth and phytochemical attributes when grown in Cdcontaminated (0.8 mM) pots. Seedlings under Cd stress had 38% less shoot length (SL), 53% total soluble sugar (TSS) and 57% protein content. However, superoxide dismutase (SOD), hydrogen peroxide (H2O2) and malondialdehyde (MDA) increased by 51%, 37% and 34%, respectively, under Cd stress. Beside this, activities such as peroxidase (POX) also elevated in the plants subjected with Cd-stress. In contrast, Mel (100 µm) as foliar spray and SiO-NPs (100 mg/L) as root dipping reduced oxidative stress in rice seedlings under Cd stress by reducing reactive oxygen species (ROS) generation. Furthermore, the application of Mel and/or SiO-NPs significantly increased the activity of antioxidative enzymes that scavenge ROS. The combined application of SiO-NPs and Mel increased growth, gas exchange and photosynthetic attributes, chlorophyll value, and protein content. It causes alleviation in the activity of SOD, CAT and POX by 73%, 62% and 65%, respectively. Overall, this study findings show that Mel and/or SiO-NPs can potentially protect the rice crop against oxidative damage under Cd stress.